## Related questions with answers

Question

Solve each multi-step equation. $-m+3(m+1)=11$

Solution

VerifiedStep 1

1 of 2To solve an equation, we isolate the variable using different properties of equality.

We are given the equation::

$-m+3(m+1)=11$

Use the distributive property: $a(b+c)=ab+ac$

$-m+3m+3=11$

$2m+3=11$

Subtract $3$ from both sides:

$2m+3-3=11-3$

$2m=8$

Divide both sides by $2$:

$\dfrac{2m}{2}=\dfrac{8}{2}$

$\color{#c34632}m=4$

## Create a free account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Create a free account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Recommended textbook solutions

#### enVision Algebra 1

1st Edition•ISBN: 9780328931576Al Cuoco, Christine D. Thomas, Danielle Kennedy, Eric Milou, Rose Mary Zbiek3,653 solutions

#### Big Ideas Math Integrated Mathematics II

1st Edition•ISBN: 9781680330687Boswell, Larson4,539 solutions

## More related questions

- prealgebra

1/4

- prealgebra

1/7